Severe warm-rolling mediated microstructure and texture of equiatomic CoCrFeMnNi high entropy alloy: A comparison with cold-rolling. (February 2021) - Saha, J.; Ummethala, G.; Malladi, S.R.K.; Bhattacharjee, P.P.
Abstract: The effect of severe warm-rolling on the microstructure and texture development in FCC equiatomic CoCrFeMnNi HEA was investigated in the present work. For this purpose, the HEA was warm-rolled to 90% reduction in thickness at 600 °C and annealed for 1 h at temperatures up to 1200 °C. To highlight the effect of warm-rolling, a critical comparison was made with similarly deformed and annealed cold-rolled HEA. The warm-rolled HEA showed an ultrafine lamellar microstructure, which was, however, significantly coarser than the cold-rolled HEA. The significantly coarser microstructure in the warm-rolled HEA could be attributed to the dynamic annihilation of dislocations during deformation. Warm-rolled HEA showed a pure metal or copper type texture instead of a predominantly brass type texture in the cold-rolled HEA. The stark differences in the deformation texture could be attributed to the increase in the SFE at the temperature of warm-rolling, which promoted more homogeneous deformation by dislocation slip over twin mediated deformation and extensive shear band formation. The lower stored energy and coarser deformation structure of the warm-rolled HEA resulted in higher recrystallization temperature, and consistently larger recrystallized grain size than the cold-rolled HEA. Annealing also resulted in the weakening of the recrystallization texture owing to the absence of strong preferential nucleation or growth. The HEA warm-rolled and annealed at 750 °C resulted in a fine-grained, completely recrystallized microstructure with the optimum strength-ductility combination. The present results revealed that warm-rolling could be effectively used as a processing route for tailoring microstructure and properties of CoCrFeMnNi HEA. Highlights: Microstructure and texture of warm-rolled CoCrFeMnNi HEA was compared with cold-rolled HEA. Predominantly lamellar but coarser microstructure in the warm-rolled HEA. Pure metal type and brass type textures in the warm- and cold-rolled HEAs, respectively. Consistently larger grain size in the warm-rolled HEA than cold-rolled HEA after annealing. Recrystallization texture formation was featured by absence of preferential nucleation and growth.